Synergistic effects of l-theanine and epigallocatechin gallate in alleviating ovalbumin allergy by regulating intestinal immunity through inhibition of mast cell degranulation. Issue 4 (2nd February 2023) - Xu, Wei; Song, Xianying; Qu, Qingyun; Gong, Zhihua; Xiao, Wenjun
Abstract : Ovalbumin (OVA), a commonly consumed food protein, can cause severe allergies and intestinal immune disorders. Abstract : Ovalbumin (OVA), a commonly consumed food protein, can cause severe allergies and intestinal immune disorders. l -Theanine (LTA) and epigallocatechin gallate (EGCG) regulate intestinal immunity. However, it is unclear whether an LTA and EGCG combined intervention can alleviate OVA allergy (OVA-A) by modulating intestinal-specific immunity, and it is unknown whether there is a synergistic effect between LTA and EGCG. Therefore, we treated BALB/c OVA-sensitized mice with LTA, EGCG, or a combination of both (LTA + EGCG) to investigate the effects of LTA and EGCG on intestinal-specific immunity regulation and underlying mechanisms. Female mice were intraperitoneally injected with OVA to establish OVA-sensitive mouse models. MLEO LTA + EGCG (20 mg kg −1 d −1 LTA + 80 mg kg −1 d −1 EGCG) and HLEO (30 mg kg −1 d −1 LTA + 120 mg kg −1 d −1 EGCG) exerted more beneficial effects on alleviating OVA-A (weight gain, allergy score, jejunum structure, mast cell [MC] degranulation, thymus and spleen indices) than LTA or EGCG alone ( p < 0.01). Based on the alleviation of OVA-A by LTA + EGCG, we selected MLEO mice for 16S rDNA, flow cytometry, and western blot analyses. The 16S rDNA results showed that MLEO increased the abundance of Lactobacillaceae, Lachnospiraceae, and Ruminococcaceae, and decreased that of Helicobacteraceae ( p < 0.01). The flow cytometry and western blotting results indicated that MLEO reduced the number of dendritic cells available to capture OVA, thereby lowering the Th2 immune response and decreasing the IL-4 and IL-13 levels. Meanwhile, the attenuation of the Th2 immune response inhibits the cross-linking of OVA and FcεRI, thus reducing MC degranulation and decreasing the serum HIS and mMCPT-1 levels through the FcεRI/Btk/PLCγ signaling pathway. LTA + EGCG also inhibits the Th2 immune response through the FcεRI/Lyn/Syk/PI3K/AKT signaling pathway and decreases the serum IL-4 and IL-13 levels. Notably, LTA + EGCG promotes the Treg and Th1 immune responses and inhibits the Th17 immune response, altering the levels of the corresponding cytokines. Therefore, LTA + EGCG can synergistically alleviate OVA-A by regulating intestinal immunity through MC degranulation inhibition.